I want to live! - Wanger, Walter; Wise, Robert; Figaro, Inc.; MGM Home Entertainment Inc. (New York : MGM Home Video, 2002)
In this powerful film based on a true story, Barbara Graham is accused and convicted of murder. Although she maintains her innocence throughout the ordeal, she is sentenced to die in the gas chamber. The intensity mounts during the final scenes as a stay of execution is sought
Originally released as a motion picture in 1958
Original score, John Mandel ; screenplay, Nelson Gidding and Don Mankiewicz
Cast : Susan Hayward, Simon Oakland, Virginia Vincent, Theodore Bikel, Wesley Lau, Philip Coolidge, Lou Krugman
Keywords: Trials (Murder) -- United States -- Drama; Death row inmates -- United States -- Drama